Deep structural inhomogeneities of the bottom of the central segment of the Shackleton Fracture Zone (Drake Passage) according to geophysical research - V. D. Solovyov; V. G. Bakhmutov; I. N. Korchagin; S. P. Levashov (Ukrainian Antarctic Journal, 2010)
The Ukrainian Antarctic expeditions acquired new geophysical data along profiles across Drake Passage with the aim of its crustal structure studying. New geophysical interpretation about the earth's crust structure within the central segment of the Drake Passage and the Shackleton Fracture Zone (SFZ) is made. The new data reveal the asymmetrical deep crustal structure of the area of intersection between the Shackleton Fracture Zone and the West Scotia Ridge. The results of 2D density modeling show that the SFZ is characterized by thickened oceanic crust. This zone is bordered by local areas of crustal thinning within some kilometers. The anomalous distributing of density and electrical parameters and the crustal thickening may be the result of possible deep crustal transformation of areas with the former continental crust in the Drake Passage and  the West Skotia Sea or the result of expression of the regional compressional stress field.